Acrylic painting : step by step - Swimm, Tom (Artist's library series, 2005)
Beginners and accomplished artists alike are attracted to the beauty and versatility of acrylic painting. In this comprehensive book, you will find all the instruction and inspiration you need to master the medium or improve your painting skills. Accomplished artist Tom Swimm guides you step by step through 12 stunning acrylic projects, offering easy-to-follow instructions along with his personal artistic insights. Acrylic Painting Step by Step covers dozens of beginning and advanced acrylic techniques, from underpainting and glazing to impasto and texturizing. You will learn to paint a varie.